The Role of Bhabinkamtibmas in Preventing the Crime of Theft of Two-Wheel Motorized Vehicles in the Legal Area of Tanjung Morawa Police, Deli Serdang Police - Calvin Reinaldy Simbolon (Advances in Police Science Research Journal, 2021)
The background of this research is because the motor vehicle theft case is still found in the jurisdiction of the Tanjung Morawa Police, so it is necessary to evaluate the role of Bhabinkamtibmas in preventing the motor vehicle theft case in the area. The problem in this research is how to describe the criminal act of theft of two-wheeled motorized vehicles at the Tanjung Morawa Police? What is the role of Bhabinkamtibmas in preventing the crime of theft of two-wheeled motorized vehicles at the Tanjung Morawa Police, the jurisdiction of Deli Serdang Police? what are the factors that influence the role of Bhabinkamtibmas in order to prevent the crime of theft of two-wheeled motorized vehicles at the Tanjung Morawa Police, the jurisdiction of the Deli Serdang Police. The analysis in this study is a role theory to analyze the role of Bhabinkamtibmas in preventing motor vehicle theft, crime prevention theory to analyze preventive actions taken by Bhabinkamtibmas in preventing motor vehicle theft and management theory to analyze the implementation of Bhabinkamtibmas role in regulating activities in terms of motor vehicle theft prevention. This research approach is a qualitative approach, with field research methods. The focus of this research explains the role of Bhabinkamtibmas in preventing two-wheeled motor vehicle theft crime at the Tanjung Morawa Police. Data collection techniques were carried out through interviews, observation and document study. Data analysis techniques include data reduction, data presentation and data verification. The results of this study show that the description of motor vehicle theft at the Tanjung Morawa Police has decreased from 2019 to 2020. motor vehicle theft perpetrators are, on average, 18-30 years old, conducted at 03.00-05.00 WIB. The motor vehicle theft mode uses the key of T, metal cutting scissors, and the use of fake tickets. The role of Bhabinkamtibmas in order to prevent motor vehicle theft is to apply proper management by implementing various crime prevention strategies such as social crime prevention, situational crime prevention and community-based crime prevention. The inhibiting factor in preventing motor vehicle theft comes from the placement of the fostered area far from the residence of the Bhabinkamtibmas members, limited facilities and infrastructure and the lack of positivity for the community in accepting Bhabinkamtibmas efforts in preventing criminal acts of motor vehicle theft.